Clinical characteristics and predictors of outcomes of hospitalized patients with COVID-19 in a multi-ethnic London NHS Trust: a retrospective cohort study - Perez,Guzman PN; Daunt,A; Mukherjee,S; Crook,P; Forlano,R; Kont,M; Lochen,A; Vollmer,M; Middleton,P; Judge,R; Harlow,C; Soubieres,A; et al. (Clinical Infectious Diseases, 2020)
Background: Emerging evidence suggests ethnic minorities are disproportionatelyaffected by COVID-19. Detailed clinical analyses of multi-cultural hospitalized patientcohorts remain largely undescribed.Methods: We performed regression, survival andcumulative competing risk analyses to evaluate factors associated with mortality inpatients admitted for COVID-19 in three large London hospitals between February 25and April 5, censored as of May 1, 2020.Results: Of 614 patients (median age 69years, (IQR 25) and 62% male), 381 (62%) had been discharged alive, 178 (29%)died and 55 (9%) remained hospitalized at censoring. Severe hypoxemia (aOR 4.25,95%CI 2.36-7.64), leukocytosis (aOR 2.35, 95%CI 1.35-4.11), thrombocytopenia (aOR1.01, 95%CI 1.00-1.01, increase per 10x9decrease), severe renal impairment (aOR5.14, 95%CI 2.65-9.97), and low albumin (aOR 1.06, 95%CI 1.02-1.09, increase per gdecrease) were associated with death. Forty percent (244) were from black, Asian andother minority ethnic (BAME) groups, 38% (235) white and for 22% (135) ethnicity wasunknown. BAME patients were younger and had fewer comorbidities. Whilst theunadjusted odds of death did not differ by ethnicity, when adjusting for age, sex andcomorbidities, black patients were at higher odds of death compared to whites (aOR1.69, 95%CI 1.00-2.86). This association was stronger when further adjusting foradmission severity (aOR 1.85 95% CI 1.06-3.24). Conclusions: BAME patients were over-represented in our cohort and, whenaccounting for demographic and clinical profile of admission, black patients were atincreased odds of death. Further research is needed into biologic drivers of differencesin COVID-19 outcomes by ethnicity.